2013
DOI: 10.3109/02699052.2012.729290
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of symptoms and neurocognitive outcomes in youth with concussion vs orthopaedic injuries

Abstract: As expected, more post-concussion symptoms were initially reported by children and adolescents with mTBI vs orthopaedic injury, but there was no difference at 3 months. The BRIEF and ImPACT cognitive measures did not differentiate concussed subjects from controls, with the exception of concussed subjects' lower performance on a visual memory test at both initial assessment and at 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…Hence, further research is needed to improve the understanding of the etiology of PCS, specifically regarding the differential influence of injury and non-injury related factors on long-term PCS. Consistent with previous studies, our results showed that socio-behavioral and neuropsychological outcome were comparable between children after mTBI and OI in the postacute period (Asarnow et al, 1995;Babikian et al, 2011;Maillard-Wermelinger et al, 2009;Rieger et al, 2013). With the exception of an improved processing speed over time, no further group or time changes were found.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, further research is needed to improve the understanding of the etiology of PCS, specifically regarding the differential influence of injury and non-injury related factors on long-term PCS. Consistent with previous studies, our results showed that socio-behavioral and neuropsychological outcome were comparable between children after mTBI and OI in the postacute period (Asarnow et al, 1995;Babikian et al, 2011;Maillard-Wermelinger et al, 2009;Rieger et al, 2013). With the exception of an improved processing speed over time, no further group or time changes were found.…”
Section: Discussionsupporting
confidence: 92%
“…There are limited comparable data on neurocognitive testing in the ED, with most assessments occurring in the sub‐acute time period. In similar studies, results have been mixed, with slower reaction times being demonstrated by the majority, but not all studies . Visual memory dysfunction was also found in mTBI patients; however, equivocal findings have also been noted .…”
Section: Discussionmentioning
confidence: 96%
“…In similar studies, results have been mixed, with slower reaction times being demonstrated by the majority, but not all studies . Visual memory dysfunction was also found in mTBI patients; however, equivocal findings have also been noted . Measures of executive functioning are not commonly included in acute testing; with just one previous study finding no differences between mTBI and orthopaedic controls on the CNS Vital Signs computerised battery Stroop task and shifting attention tests .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using computerized cognitive testing (ImPACT) found visual memory deficits in 8 to 17 year olds with mTBIs who were tested within 72 h of the injury, 12 but not an acute effect on processing speed or reaction time. Interestingly, these latter cognitive domains of psychomotor speed and reaction time (but not memory performance) were significantly worse in an adult sample with mTBI who were tested using ImPACT in the ED within 48 h of their injury.…”
Section: Discussionmentioning
confidence: 99%
“…10 In contrast, two studies using computerized cognitive assessment techniques found significant differences in cognitive scores, compared to population norms, 11 and orthopedic controls. 12 Nance and colleagues administered the Immediate Postconcussion Assessment and Cognitive Test (ImPACT), a brief computerized measure of cognition, to 11 to 17 yearolds who were hospitalized after an mTBI. 11 At a mean duration of 2.1 days post-mTBI, hospitalized patients had cognitive scores that were lower than population values (e.g., approximately one third had all cognitive scores below the 25th percentile).…”
Section: Introductionmentioning
confidence: 99%